Synthesis and optimization of a selective magnetic molecular imprinted polymer toward quantification of tetracycline in food samples - Zeb, Shakeel [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Tetracycline is an exceptionally important antibiotic that is frequently utilized for the treatment of bacterial disorders and respiratory conditions in both humans and animals. Both the prevention of bacterial infections and the treatment of advanced stages of bacterial growth are common applications for this antibiotic in the poultry farming industry. In order to detect tetracycline antibiotics in food samples, magnetic molecularly imprinted polymers (mag-MIP) were synthesized and tested in this work. High-performance liquid chromatography (HPLC), and fluorescence spectroscopy analysis were applied to investigate the adsorption experiments. Moreover, the tetracycline antibiotic was identified using an alternate electrochemical sensor technique. In order to make magnetic nanoparticles, iron salts like FeCl3.6H2O and FeCl2.4H2O were used; they were then modified using methacryloxypropyltrimethoxysilane (MPS). Initially, part of the research was based on HPLC and Spectro-fluorometer analysis: Magnetic nanoparticles, methacrylic acid (functional monomer), ethylene-glycol-dimethacrylate (cross-linker), and benzoyl peroxide (radical initiator) were all used in calculated proportions to synthesize the mag-imprinted polymer. In the second segment, which deals with electrochemical investigation, the mag-imprinted polymer was prepared by mixing the appropriate amount of magnetic nanoparticles, acrylic acid (functional monomer), ethylene-glycol-dimethacrylate (cross-linker), and 2,2 azo-bis-isobutyronitrile (radical initiator). The techniques of field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), and Fourier transform infrared (FTIR) were utilized in order to explore the morphological, and chemical characteristics of synthesized materials. The analytical curve was produced using the range from 1.0 × 10-5 mol L-1 to 8.0 × 10-5 mol L-1. The adsorption capacity of mag-MIP at equilibrium was 4.123 mg g-1 and adsorption process followed the Langmuir isotherm, and Temkin model and pseudo-2nd-order reaction kinetic. The proposed mag-polymer materials were applying in food samples using two different concentrations of tetracycline (1.7 × 10-5 and 2.5 × 10-5 mol L-1) obtaining recoveries ranging from 73.2-87.3% (HPLC) and 90.53–103.7% (Spectro-fluorometer), respectively. In electrochemical sensor: Tetracycline detection was carried out under optimal conditions utilizing square wave voltammetry, 15 mg of mag-MIP (on carbon paste), and the time is 80 seconds. Using this method, well-defined peaks ranging from 0.5 to 1.0 V vs. Ag/AgCl (KClsat) were produced. Analytical curves were constructed using the second peak at 0.83 V, yielding the following results: linear range of 5.0 ×10-7 to 4.0 ×10-5 mol L-1 (R2 of 0.9993), the limit of detection (LOD) of 1.5 ×10-7 µmol L-1, and repeatability of 2.82%. The results of the selectivity analysis showed that the suggested electrochemical sensor is highly efficient for tetracycline determination. The sensor was effectively used to identify tetracycline in commercial and raw milk samples, with recovery rates ranging from 93 to 103%.

A tetraciclina é um antibiótico excepcionalmente importante que é frequentemente utilizado para o tratamento de distúrbios bacterianos e condições respiratórias em humanos e animais. Tanto a prevenção de infecções bacterianas quanto o tratamento de estágios avançados de crescimento bacteriano são aplicações comuns desse antibiótico na indústria avícola. Para detectar antibióticos tetraciclinas em amostras de alimentos, polímeros magnéticos de impressão molecular (mag-MIP) foram sintetizados e testados neste trabalho. Cromatografia líquida de alta eficiência (HPLC) e análise de espectroscopia de fluorescência foram aplicadas para investigar os experimentos de adsorção. Além disso, o antibiótico tetraciclina foi identificado usando uma técnica de sensor eletroquímico alternativo. Para fazer nanopartículas magnéticas, foram utilizados sais de ferro como FeCl3.6H2O e FeCl2.4H2O; eles foram então modificados usando metacriloxipropiltrimetoxisilano (MPS). Inicialmente, parte da pesquisa foi baseada em HPLC e análise de espectrofluorímetro: nanopartículas magnéticas, ácido metacrílico (monômero funcional), etileno-glicol-dimetacrilato (reticulador) e peróxido de benzoíla (iniciador radical) foram todos usados em proporções calculadas para sintetizar o polímero impresso em mag. No segundo segmento, que trata da investigação eletroquímica, o polímero impresso em mag foi preparado misturando a quantidade apropriada de nanopartículas magnéticas, ácido acrílico (monômero funcional), etileno-glicol-dimetacrilato (reticulador) e 2,2 azo-bis-isobutironitrila (iniciador radical). As técnicas de microscopia eletrônica de varredura de emissão de campo (FESEM), microscopia eletrônica de transmissão de alta resolução (HRTEM) e infravermelho por transformada de Fourier (FTIR) foram utilizadas para explorar as características morfológicas e químicas dos materiais sintetizados. A curva analítica foi produzida utilizando o intervalo de 1,0 × 10-5 mol L-1 a 8,0 × 10-5 mol L-1. A capacidade de adsorção do mag-MIP no equilíbrio foi de 4,123 mg g-1 e o processo de adsorção seguiu o modelo de isoterma de Langmuir e Temkin cinética de reação de pseudo- 2ª ordem. Os materiais mag-polímeros propostos foram aplicados em amostras de alimentos usando duas concentrações diferentes de tetraciclina (1,7 × 10-5 e 2,5 × 10-5 mol L-1) obtendo recuperações variando de 73,2-87,3% (HPLC) e 90,53-103,17% (Espectrofluorímetro), respectivamente. No sensor eletroquímico: A detecção de tetraciclina foi realizada em condições ideais utilizando voltametria de onda quadrada, 15 mg de mag-MIP (em pasta de carbono) e o tempo é de 80 segundos. Usando este método, picos bem definidos variando de 0,5 a 1,0 V vs. Ag/AgCl (KClsat) foram produzidos. As curvas analíticas foram construídas usando o segundo pico em 0,83 V, produzindo os seguintes resultados: faixa linear de 5,0 ×10-7 a 4,0 ×10-5 mol L-1 (R2 de 0,9993), o limite de detecção (LOD) de 1,5 ×10-7 mol L-1 e repetibilidade de 2,82%. Os resultados da análise de seletividade mostraram que o sensor eletroquímico sugerido é altamente eficiente para determinação de tetraciclina. O sensor foi efetivamente utilizado para identificar tetraciclina em amostras de leite comercial e cru, com taxas de recuperação variando de 93 a 103%.
Síntese e otimização de um polímero molecular magnético seletivo para quantificação de tetraciclina em amostras de alimentos
Keywords: Magnetic nanoparticles; Molecularly imprinted polymers; Biomimetic sensor; Electrochemical sensor; Tetracycline